Knowledge, Policy and Practice in Education and the Struggle for Social Justice Essays Inspired by the Work of Geoff Whitty - Brown, Andrew; Wisby, Emma (UCL Press, 2020)
For 50 years, educator and sociologist Geoff Whitty resolutely pursued social justice through education, first as a classroom teacher and ultimately as the Director of the Institute of Education in London. The essays in this volume - written by some of the most influential authors in the sociology of education and critical policy studies - take Whitty's work as the starting point from which to examine key contemporary issues in education and the challenges to social justice that they present. Set within three themes of knowledge, policy and practice in education, the chapters tackle the issues of defining and accessing 'legitimate' knowledge, the changing nature of education policy under neoliberalism and globalization, and the reshaping of teacher workplaces and professionalism - as well as attempts to realize more emancipatory practice. Whitty's scholarship on what constitutes quality and impact in educational research is also explored. Together, the essays open a window on a life in the sociology of education, the scholarly community of which it was part, and the facets of education policy, practice and research that they continue to reveal and challenge in pursuit of social justice. They celebrate Whitty as one of the foremost sociologists of education of his generation, but also as a friend and colleague. And they highlight the continued relevance of his contribution to those seeking to promote fairer and more inclusive education systems.